Використання принципів Clean Architecture у застосунках на Dart та Flutter - Тєльний, М. В. (ХНУРЕ, 2023)
This work explores the use of Clean Architecture principles in applications written in the Dart programming language using the Flutter framework. The advantages of Clean Architecture lie in its ability to break down an application into logical components, reduce dependencies on external frameworks and libraries, and simplify the process of testing and maintaining applications in the future. In this work, the principles of Clean Architecture, such as Dependency Rule and Dependency Inversion, will be investigated, as well as their application in Dart and Flutter applications. The main layers of the architecture and their purposes are described